2006
DOI: 10.1093/molehr/gal097
|View full text |Cite
|
Sign up to set email alerts
|

A new paradigm for profiling testicular gene expression during normal and disturbed human spermatogenesis

Abstract: The aim of this study was to identify gene expression patterns of the testis that correlate with the appearance of distinct stages of male germ cells. We avoided the pitfalls of mixed pathological phenotypes of the testis and circumvented the inapplicability of using the first spermatogenic wave as done previously on rodents. This was accomplished by using 28 samples showing defined and highly homogeneous pathologies selected from 578 testicular biopsies obtained from 289 men with azoospermia (two biopsies eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 42 publications
3
48
0
3
Order By: Relevance
“…10 For validation of the gene-expression data described here, we used a second, independent dataset of human spermatogenesis. 11 Except for EZH2 and MBD1, concordant expression profiles were found. The apparent discrepancy regarding the latter two genes may, at least in the case of MBD1, be because of different probes on the two array platforms and the presence of different splice forms (see below).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…10 For validation of the gene-expression data described here, we used a second, independent dataset of human spermatogenesis. 11 Except for EZH2 and MBD1, concordant expression profiles were found. The apparent discrepancy regarding the latter two genes may, at least in the case of MBD1, be because of different probes on the two array platforms and the presence of different splice forms (see below).…”
Section: Discussionmentioning
confidence: 89%
“…To corroborate these findings, genes displayed in the heatmap of Figure 3 were interrogated on a dataset from a completely different, single-oligonucleotide microarray platform 11 by using the intersection obtained from HUGO annotations. This cross-platform comparison validates the expression changes described here and obviates the need to validate single genes, as has been shown in a study in which 93% of genes common to two microarray platforms could be confirmed in their differential expression by quantitative real-time PCR 12 .…”
Section: Expression Of Snurf -Snrpn Upstream Transcriptsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent microarray studies have assessed global gene expression analysis in testicular biopsies from infertile men to identify the genes critical for spermatogenesis (Fox et al, 2003;Rockett et al, 2004;Ellis et al, 2007;Feig et al, 2007;von Kopylow et al, 2010;Chalmel et al, 2012). In these studies specific germ cell transcription patterns are inferred from infertile testicular phenotypes in men and a pattern of significantly decreased regulated genes has been attributed to the degree of spermatogenic failure and the loss of specific stages of germ cells.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to their utilisation for in situ promoter studies, the cells were genetically characterised and were found to express Pgk-2 and protamine transcripts (data not shown). Pgk-2 transcription is known to occur only in post-meiotic germ cells (Feig et al, 2007), while protamine is only expressed in round spermatids stage (Hecht, 1986). To understand testis-specific gene regulation during spermatogenesis, it is essential to analyse in detail the cis-elements in pro-moters that are expressed at similar stages of spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%